Dialect culture and the utilization of public health service by rural migrants: Insights from China - Zhao, Qingjun; Xu, Siyu; Aziz, Noshaba; He, Jun; Wang, Yue (Frontiers in Public Health, 2022)
The right to health is a fundamental human right for human beings to live in dignity. Everyone has the right to enjoy the fair and accessible highest standard of health by utilizing public health services. However, access to essential public health services also highly depends on the dialect culture. It is believed that the dialect culture also influences the efficiency of public health policies. To explore the phenomenon empirically, the current study utilized data sourced from geographical distribution information of Chinese dialects and the China Migrants Dynamic Survey for 2017. The study employed the Probit, IVprobit, and Eprobit models to estimate the impact of dialect culture on migrants’ use of public health services. The findings revealed that the dialect culture significantly hinders the migrants’ utilization of public health services. Further, by employing heterogeneity analysis, the findings revealed that the results are more pronounced in migrants, born after 1980, and are female with low educational background and also those migrants having local medical experiences and moving towards non-provincial cities. Finally to explore the mechanism of dialect culture influencing migrants’ public health service, the study employed mediation analysis and KHB Method. The findings revealed that information transmission, health habits, social capital, and cultural identity are the potential pathways influencing the migrants’ use of public health services. The findings conclude that rural-to-urban migrants’ access to public health services is influenced by their cultural adaptation. Hence, the study proposes that the government should amend the policy inefficiency concerns caused by cultural differences and strengthen the regional cultural exchanges to build trust.